ETOS KERJA ISLAMI DAN KESEJAHTERAAN KARYAWAN PADA PT. ADIRA DINAMIKA MULTI FINANCE SYARIAH - NURFITRI HIDAYANTI; BUSAINI BUSAINI; MOH. HUZAINI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". This work ethic is dynamically always influenced by several factors, both internal and external. This study aims to see the concept of work in the view of Islam, the application of Islamic work ethic and characteristics of Islamic work ethic for employees of PT. Adira Dinamika Multi Finance Syariah, Tbk branch of Mataram. The methods used are qualitative methods and data collection by using triangulation consisting of observation, interview and documentation so that they can explore the complete information about the Islamic work ethic in PT. Adira Dinamika Multi Finance Syariah, Tbk branch of Mataram. The results of this study found that of the seven informants are said to be less able to work in accordance with Islamic views, the characteristics of the Islamic work ethos that is less visible from the seven informants seen when they often come late, less willing in doing the work, less honest, not istiqomah, sometimes happy to serve customers sometimes less happy. If viewed the level of welfare from employees of PT. Adira Dinamika Multi Finance Syariah, Tbk branch of Mataram from the seven informants have fulfilled the indicators of Islamic welfare (maqashid syariah) although in every person all components always exist like 1) Maintaining religion, 2) Maintaining the soul, 3) Maintaining the mind, 4) maintaining the offspring, 5) Maintain wealth.